The Strategic Pedagogical Role of Code-Switching in Enhancing EFL Classroom Interaction: Insights from MAN 1 Polewali Mandar - Marliana, Rina; Adriani; Musdikawati, Sri (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
Code-switching is a common linguistic strategy in bilingual or multilingual communities, particularly in English as a Foreign Language (EFL) classrooms. This study investigates the pedagogical functions of code-switching employed by teachers in EFL classroom interactions at MAN 1 Polewali Mandar. Using a descriptive qualitative methodology, data were collected through classroom observations and semi-structured interviews with an English teacher and two classes. The findings reveal that code-switching serves five key functions: emphasizing important points, clarifying questions, checking vocabulary comprehension, reinforcing requests, and checking understanding. These functions facilitate better communication, foster engagement, and enhance students' learning outcomes. The study highlights the strategic value of code-switching in overcoming linguistic barriers, ensuring inclusivity, and fostering an effective learning environment in multilingual classrooms. Practical implications suggest that teachers should utilize code-switching purposefully to address students' needs while gradually encouraging active use of English.